Proyecto de factibilidad para la producción de cuy ahumado y su comercialización en la ciudad de Loja - Sánchez Sarmiento, Tatiana Elizabeth (2015)
This project aims to study the feasibility of smoked guinea pig production and marketing in the city of Loja, Loja Canton province of Loja. Throughout the years, our guinea pig breeding livestock culture has been crudely -ancestral and in order to feed his family, during the year’s progress and this way of life and work is to generate employment and increase their level of income. The guinea pig meat consumption is growing due to its high nutritional value, low in fat and good flavor. The smoky cuy gives us many benefits and advantages which are summarized in excellent preservative in places where there is no electricity, very healthy meat because it does not demand of oil and / or flavorings for preparation, appetizing meat for its aroma and flavor. Methods and techniques is established in the research process by which it was determined that the processing and marketing of smoked guinea pig is void in our midst, behold their importance to exploit this huge market. As a primary source of information for each producer survey was conducted; and secondary consumers of guinea pig meat In this case a sample of the population in urban parishes in the city of Loja and determine certain important aspects that helped the development of this project. In the market research it determined that there is a potential demand of 173,392 to a real demand for 767,620 units of guinea pig, and effective demand of 138,171 for the first year and an unmet demand of 123,351 a year. The technical study infrastructure needs , capacity, machinery , aims to cover , location, project engineering and process description of the product is established , establishing for the first year an installed capacity of 24,000 units covering 19.45 % of unsatisfied demand Engineering Project revealing every step of the production process, the frame location and micro location of the project was also performed, the legal bow and legal status was established. Regarding the study of the organization of the company producing smoked guinea pig, he will be represented by the Manager, whose name will be “smoked Co. Cuysitos. Ltd.“, Incorporated as a limited company. The financial study shows numerically that the total value of the investment is $ 46,287.08 of which 56.79 % contributed by the shareholders and the remaining capital was financed by a loan from the Bank of Machala at an interest rate 11 % annual. Net cash flow for the first year of $ 12,300.34 is estimated to increase in the following years. The financial evaluation shows the following results: A positive NPV of $ 8,008.32; The IRR of 47.42 %, the capital invested is recovered in 03 years, 03 months, 07 days, and for every dollar invested a gain of $ 1 will be obtained with thirty-four cents and the project can support an increase cost of 0.99 % and a decrease in revenue of 0.99 %, which indicates the effectiveness of the project With the culmination of conclusions and recommendations is determined according to studies conducted in this project that will help them better development of further research conducted on the basis of this project arise